The Non-Evolutionary and Non-Benign Character of Stylized Facts. Issue 2 (3rd April 2021) - Powell, Jacob
Abstract: This article highlights the potential of stylized facts to take on a non-evolutionary and non-benign character. Two stylized facts are used as primary examples throughout the article: the inverse trade-off between changes in unemployment and changes in price level (i.e., the Phillips curve) and that countries with debt-to-GDP ratios in excess of 90 percent experience lower economic growth. The insights of Pierre Bourdieu will be drawn upon to understand the socialization processes which create common sense understandings of our world that are non-evolutionary and non-benign, what Bourdieu calls doxic understandings. Doxic understandings of the world are inherently ceremonial and antithetical to an evolutionary approach. To overcome these problems, does not mean the elimination of heuristics; but rather, a continual application of reflexivity. Reflexivity is a process, where the researcher is continually interrogating what is being taken for granted in their own methods and logic, to ensure these are grounded in instrumental reasoning. Reflexivity is necessary to safeguard economics and the public against doxic understandings, and is a necessary condition of realism in analysis.